Pengaruh Gaji dan Lingkungan Kerja Terhadap Loyalitas Karyawan di CV. ANJASA Baja Ringan Semarang - Sigit Kharisma; Kustiyono Kustiyono (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2020)
The research objective, entitled The Effect of Salary and Work Environment on Employee Loyalty in CV. ANJASA Baja Ringan Semarang is to determine, the effect of salary on employee loyalty, the influence of the work environment on employee loyalty, the effect of salary and work environment on employee loyalty. The sample in this study amounted to 30 respondents who were distributed to employees. The data analysis method used is quantitative analysis using data quality test, classical assumption test, t statistical test, F statistical test, multiple linear regression analysis test, and the coefficient of determination.